Does b1000–b0 Mismatch Challenge Diffusion-Weighted Imaging–Fluid Attenuated Inversion Recovery Mismatch in Stroke?. Issue 3 (March 2016) - Geraldo, Ana Filipa; Berner, Lise-Prune; Haesebaert, Julie; Chabrol, Aurélie; Cho, Tae-Hee; Derex, Laurent; Hermier, Marc; Louis-Tisserand, Guy; Chamard, Leila; Klaerke Mikkelsen, Irene; Ribe, Lars; Østergaard, Leif; et al.
Abstract : Background and Purpose—: Our aim was to explore whether the mismatch in lesion visibility between b1000 and b0 images is an alternative to mismatch between diffusion-weighted imaging and fluid-attenuated inversion recovery imaging as a surrogate marker of stroke age. Methods—: We analyzed patients from the European multicenter I-KNOW database. Independent readers assessed the visibility of ischemic lesions of the anterior circulation on b0 and fluid-attenuated inversion recovery imaging images. The signal-intensity ratio for b0 and fluid-attenuated inversion recovery imaging images was also measured from the segmented stroke lesion volume on b1000 images. Results—: This study included 112 patients (68 men; mean age, 67.4 years) with stroke onset within (n=85) or longer than (n=27) 4.5 hours. b1000–b0 mismatch identified patients within 4.5 hours of stroke onset with moderate sensitivity (72.9%; 95% confidence interval [CI], 63.5–82.4) and specificity (70.4%; 95% CI, 53.2–87.6), high positive predictive value (88.6%; 95% CI, 81.1–96.0), and low negative predictive value (45.2%; 95% CI, 30.2–60.3). Global comparison of b1000–b0 mismatch with diffusion-weighted imaging–fluid-attenuated inversion recovery imaging mismatch (considered the imaging gold standard) indicated high sensitivity (85.9%; 95% CI, 78.2–93.6), specificity (91.2%; 95% CI, 76.3–98.1), and positive predictive value (96.7%; 95% CI, 88.0–99.1) and moderate negative predictive value (73.8%; 95% CI, 60.5–87.1) of this new approach. b0 signal-intensity ratio ( r =0.251; 95% CI, 0.069–0.417; P =0.008) was significantly although weakly correlated with delay between stroke onset and magnetic resonance imaging. Conclusions—: b1000–b0 mismatch may identify patients with ischemic stroke of the within 4.5 hours of onset with high positive predictive value, perhaps constituting an alternative imaging tissue clock.